2013
DOI: 10.3389/fnbeh.2013.00153
|View full text |Cite
|
Sign up to set email alerts
|

The three principles of action: a Pavlovian-instrumental transfer hypothesis

Abstract: Pavlovian conditioned stimuli can influence instrumental responding, an effect called Pavlovian-instrumental transfer (PIT). During the last decade, PIT has been subdivided into two types: specific PIT and general PIT, each having its own neural substrates. Specific PIT happens when a conditioned stimulus (CS) associated with a reward enhances an instrumental response directed to the same reward. Under general PIT, instead, the CS enhances a response directed to a different reward. While important progress has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
(80 reference statements)
5
42
0
Order By: Relevance
“…This is supported by the fact that responding was elevated even during the first pre-CS interval, before any cue presentation. This interpretation is consistent with a recent theoretical model of PIT put forth by Cartoni et al (2013), which argues that behavioral inhibition is in fact necessary for specific PIT since responding is not affected by a cue that has been paired with a different action and reward. Our findings add to this model that behavioral inhibition is necessary not only in the presence of unpaired cues (the basis for specific PIT), but also at baseline within the reward-associated context.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This is supported by the fact that responding was elevated even during the first pre-CS interval, before any cue presentation. This interpretation is consistent with a recent theoretical model of PIT put forth by Cartoni et al (2013), which argues that behavioral inhibition is in fact necessary for specific PIT since responding is not affected by a cue that has been paired with a different action and reward. Our findings add to this model that behavioral inhibition is necessary not only in the presence of unpaired cues (the basis for specific PIT), but also at baseline within the reward-associated context.…”
supporting
confidence: 91%
“…IlPFC sends a dense glutamatergic projection to NAcS, a structure that is itself necessary for specific PIT (Corbit and Balleine 2011), and this projection is known to inhibit inappropriate reward seeking (Vertes 2004;Peters et al 2008Peters et al , 2009Bossert et al 2012). Such behavioral inhibition may also be an important element of specific PIT, as responding is not invigorated by a cue that has been paired with a different reward and response (Cartoni et al 2013). …”
mentioning
confidence: 99%
“…The invigoration of instrumental activity induced by the sucrose-predictive cue could be interpreted to reflect primarily the general (rather than specific) form PIT, because the stimulus invigorated responding on an action that, in training, earned a distinct, grape-flavored polycose reward (Dickinson & Balleine 2002, Cartoni et al 2013, Fanselow & Wassum 2015, Balleine 1994, Dickinson & Balleine 1994). Indeed, sucrose and polycose work through separate taste channels in the rat (Sclafani 1991, Ackroff et al 1993) and were confirmed here to be discriminable.…”
Section: Discussionmentioning
confidence: 99%
“…In the end, this PIT paradigm allowed us to look at the force ratio between hands as a measure for the so-called “specific PIT” and at the time spent inside the target meaning how long they held the cursor at the required target force level or above as a measure for “general PIT”. A specific PIT is when a Pavlovian stimulus associated with a particular outcome selectively enhances the instrumental responding associated with that specific outcome (Corbit and Balleine, 2005; Cartoni et al, 2013). For example, participants squeeze more with their dominant hand when they observe the Pavlovian stimulus because both the stimulus and response have been paired with the monetary reward previously (i.e., via stimulus-outcome-response contingency).…”
Section: Methodsmentioning
confidence: 99%